The Effect of Vocal Intonation Therapy on Vocal Dysfunction in Patients With Cervical Spinal Cord Injury: A Randomized Control Trial - Zhang, Xiaoying; Song, Yi-Chuan; Yang, De-Gang; Liu, Hong-Wei; Liu, Song-Huai; Li, Xiao-Bing; Li, Jian-Jun (Frontiers in Neuroscience, 2022)
In this study, the vocal intonation therapy (VIT) was compared with the standard respiratory therapy for people suffering from respiratory dysfunction as a result of cervical spinal cord injury (CSCI) to observe its effect on vocal quality. Thirty patients with vocal dysfunction after CSCI with the injury time of more than 3 months were screened for inclusion in the trial, and 18 patients completed the 12-weeks, each participant had 60 sessions in total in the clinical trial. All patients were allocated to the intervention group or the control group. The intervention group received VIT training and the control group received respiratory phonation therapy. Both groups were trained by professional therapists, and the training time was 30 min/day, 5 days/week, for 60 sessions for each group in a total of 12 weeks. In the Baseline (T0), mid-intervention period (after 6 weeks, T1), and after intervention (after 12 weeks, T2), the vocal quality of the two groups of patients was tested with a computer-aided real-time audio analyzer 2.1.6 (Adobe Systems, United States) for Sing-SPL (p < 0.0001), Speech-SPL (p < 0.0001), SNL (p < 0.0001), and F0 (p < 0.0001) of the intervention group were significantly improved compared with the control group. In comparing the spectrometry analysis of vocal quality for the 2 groups of participants, there was a significant difference in the results of Sing-SPL and Speech-SPL acoustic analysis in the intervention group of patients at T2 (after 12 weeks) compared to the control group. Vocal intonation therapy—music therapy can improve the speech sound quality of cervical CSCI patients and provide CSCI patients with a practical, highly operable treatment that has both functional training effects and can bring a pleasant experience that can be promoted in the medical field. This study was approved by the Ethics Committee of China Rehabilitation Research Center (CRRC) (approval No. 2019-83-1) on May 20th, 2019. It was registered with the National Health Security Information Platform, medical research registration, and filing information system (Registration No. MR-11-21-011802) on January 28th, 2021.